Role of interleukin-1beta in postoperative cognitive dysfunction. - Cibelli, M; Fidalgo, A; Terrando, N; Ma, D; Monaco, C; Feldmann, M; Takata, M; Lever, I; Nanchahal, J; Fanselow, MS; Maze, M (2010)
OBJECTIVE: Although postoperative cognitive dysfunction (POCD) often complicates recovery from major surgery, the pathogenic mechanisms remain unknown. We explored whether systemic inflammation, in response to surgical trauma, triggers hippocampal inflammation and subsequent memory impairment, in a mouse model of orthopedic surgery. METHODS: C57BL/6J, knock out (lacking interleukin [IL]-1 receptor, IL-1R(-/-)) and wild type mice underwent surgery of the tibia under general anesthesia. Separate cohorts of animals were tested for memory function with fear conditioning tests, or euthanized at different times to assess levels of systemic and hippocampal cytokines and microglial activation; the effects of interventions, designed to interrupt inflammation (specifically and nonspecifically), were also assessed. RESULTS: Surgery caused hippocampal-dependent memory impairment that was associated with increased plasma cytokines, as well as reactive microgliosis and IL-1beta transcription and expression in the hippocampus. Nonspecific attenuation of innate immunity with minocycline prevented surgery-induced changes. Functional inhibition of IL-1beta, both in mice pretreated with IL-1 receptor antagonist and in IL-1R(-/-) mice, mitigated the neuroinflammatory effects of surgery and memory dysfunction. INTERPRETATION: A peripheral surgery-induced innate immune response triggers an IL-1beta-mediated inflammatory process in the hippocampus that underlies memory impairment. This may represent a viable target to interrupt the pathogenesis of postoperative cognitive dysfunction.